Toxicidad a dosis única del extracto etanólico de Campsiandra angustifolia spruce ex benth (huacapurana) en ratones albinos cepa BALB/C - Pérez Chota, José Antonio (2025)
Every natural resource required as a therapeutic agent, requires in principle to demonstrate its safety, so determining its acute toxicity is the preliminary step before verifying its efficacy. Objective: To determine the acute toxic potential of the ethanolic extract of Campsiandra angustifolia Spruce Ex Benth (huacapurana). Methodology: Descriptive toxicological study and experimental design, which assessed clinical, biochemical and anatomical parameters in albino mice Balb / C strain. Results: The DMSO group had on average a weight differential between day 0 and the 14th day of 5.24 g (SD of 1.757), in the experimental groups weight loss predominated between 2.06 to 4.41 g) and toxicity measured by the death parameter was 60% for the root extract at 25 mg / kg and for the leaves it was 40% for the bark and leaves at a dose of 200 mg / kg; The observed microscopic variables were accompanied by vascular alterations and tissue damage in the organs examined by microscopy. Conclusions: The toxicity of the ethanolic extracts was highly toxic to the root and moderately toxic to the bark and leaves.